The Effect of Seasonal Variation on the Composition of Cow Milk in Van Province - Ozrenk, Elvan; Selcuk Inci, Sebnem (Pakistan Journal of Nutrition, 2007)
The research was performed to investigate the effects of seasonal variation on changing of cow milk components in Van province. A total of 160 cow milk samples were collected and examined from January to August of 2001. These were obtained from 12 different local points of the Van province in Turkey. The research was carried out in two periods. The first period was the winter period covering January-February-March months and the second one was the summer period covering June-July-August months. Samples were collected according to season, so that milk samples could be taken from the cows which had been fed with hay in born in winter period (January-February-March) and from those which had been fed with green grass on the Pasteur in the area in summer period. According to the results paired t test, the fat content and titratable acidity of winter and summer periods have been found significantly at p<0.05 level. Seasonal variation effect was found significantly on the protein content rate and total solids, fat, titratable acidity respectively levels of p<0.05 and p<0.01.